2022
DOI: 10.3389/fonc.2022.1022716
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of glioblastoma stem cells in the context of the immune microenvironment and geospatial organization

Abstract: Glioblastoma (GBM) is an extremely aggressive and incurable primary brain tumor with a 10-year survival of just 0.71%. Cancer stem cells (CSCs) are thought to seed GBM’s inevitable recurrence by evading standard of care treatment, which combines surgical resection, radiotherapy, and chemotherapy, contributing to this grim prognosis. Effective targeting of CSCs could result in insights into GBM treatment resistance and development of novel treatment paradigms. There is a major ongoing effort to characterize CSC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 271 publications
0
16
0
Order By: Relevance
“…GAMs and GSCs are often functionally interconnected and co-localized. Mapping of cellular distribution in human GBM revealed that striking numbers of GAMs were located around GSC clusters and, as observed with GAMS, the density of GSCs positively correlated to tumor grade ( 40 ). GAMs accumulate in perivascular regions where they produce proangiogenic factors such as VEGF and CXCL2, due to chemoattractant release from GSCs ( 36 ).…”
Section: Gams In the Gbm Microenvironmentmentioning
confidence: 87%
See 1 more Smart Citation
“…GAMs and GSCs are often functionally interconnected and co-localized. Mapping of cellular distribution in human GBM revealed that striking numbers of GAMs were located around GSC clusters and, as observed with GAMS, the density of GSCs positively correlated to tumor grade ( 40 ). GAMs accumulate in perivascular regions where they produce proangiogenic factors such as VEGF and CXCL2, due to chemoattractant release from GSCs ( 36 ).…”
Section: Gams In the Gbm Microenvironmentmentioning
confidence: 87%
“…In the presence of glioma cells, microglia produce significant amounts of TGF-β, which in turn induces production of matrix metalloproteinase 9 (MMP9) and MMP2, leading to degradation of ECM and supporting glioma stem cell invasion ( 38 ). GSCs are treatment resistant, multipotent, self-renewing cells with high heterogeneity ( 39 , 40 ). GAMs and GSCs are often functionally interconnected and co-localized.…”
Section: Gams In the Gbm Microenvironmentmentioning
confidence: 99%
“…29 Multiple lines of evidence suggest that TAMs have a role in promoting tumorigenesis, growth, invasion, and metastasis, affecting tumor metabolism. 30,31 Microhabitat maintains the essential properties of glioma stem cells, maintaining their phenotypic plasticity and thus allowing them to effectively evade surveillance by the immune system. 32 Recently single-cell analysis has emerged as a powerful tool to study the heterogeneity of gliomas at the single-cell level and to identify the cellular and molecular mechanisms involved in immune escape.…”
Section: The Overvie W Of G LI Oma Tumor Immune Micro Env Iro Nmentmentioning
confidence: 99%
“…In the stem cell microenvironment, glioma stem cells can induce differentiation of bone marrow‐derived monocytes and microglia into TAMs, the latter being the major inflammatory cell population in the TME 29 . Multiple lines of evidence suggest that TAMs have a role in promoting tumorigenesis, growth, invasion, and metastasis, affecting tumor metabolism 30,31 . Microhabitat maintains the essential properties of glioma stem cells, maintaining their phenotypic plasticity and thus allowing them to effectively evade surveillance by the immune system 32 …”
Section: The Overview Of Glioma Tumor Immune Microenvironmentmentioning
confidence: 99%
“…These results support the efficacy of this assay in more closely recapitulating the human disease as compared to KR158 cells cultured in adherent monolayer serum-containing conditions. Our previous research established the existence of a metabolic diversity within the microenvironment of human GBM, which includes fast and slow cycling cells with distinct metabolic features 1,5,16,19 . Moreover, SCCs isolated from human GBM tumors have demonstrated increased stemness, enhanced invasion, and drug resistance, pointing to their role in tumor progression and recurrence 16,19,20 .…”
Section: Introductionmentioning
confidence: 98%